2022
DOI: 10.1017/s2045796022000270
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 lockdown on mental health care use in South Africa: an interrupted time-series analysis

Abstract: Aims The coronavirus disease 2019 (COVID-19) pandemic and ensuing restrictions have negatively affected the mental health and well-being of the general population, and there is increasing evidence suggesting that lockdowns have led to a disruption of health services. In March 2020, South Africa introduced a lockdown in response to the COVID-19 pandemic, entailing the suspension of all non-essential activities and a complete ban of tobacco and alcohol sales. We studied the effect of the lockdown on mental … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…On the other hand, both the initial reduction and the subsequent increase in the trend of users attended, as well as appointments and activities performed in CMHCs reported in this study coincided with studies conducted in others mental health systems, where the same analysis (uninterrupted time series analysis) was used to estimate changes in user care in different health centers. One study in South Africa found that the levels of hospital admissions and outpatient consultations were reduced from the COVID-19 blocking measures, and during the pandemic there was a gradual recovery process in the number of hospital admissions (Wettstein et al, 2022). In other study performed in South-East England, the trend was similar to the previous study, outpatient and community care in mental health services decreased since the application of COVID-19 confinement, followed by a gradual recovery of care (Penington et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, both the initial reduction and the subsequent increase in the trend of users attended, as well as appointments and activities performed in CMHCs reported in this study coincided with studies conducted in others mental health systems, where the same analysis (uninterrupted time series analysis) was used to estimate changes in user care in different health centers. One study in South Africa found that the levels of hospital admissions and outpatient consultations were reduced from the COVID-19 blocking measures, and during the pandemic there was a gradual recovery process in the number of hospital admissions (Wettstein et al, 2022). In other study performed in South-East England, the trend was similar to the previous study, outpatient and community care in mental health services decreased since the application of COVID-19 confinement, followed by a gradual recovery of care (Penington et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This speaks to the need for greater access to and awareness of mental health and substance use services in South Africa for PWH. Though lockdowns may also have made it more challenging to access care, 12 there generally remains limited access to mental health and substance use care in the South African health system. 37 These findings speak to the ongoing need to develop and test task-shared interventions and implementation strategies to integrate mental health and substance use services into the broader health system in this context.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Medical mistrust following the onset of the pandemic has also been documented among PWH in South Africa, 10 possibly contributing to these care interruptions. Pandemic-related increases in poor mental health and substance use and on use of mental health services in South Africa 11 , 12 may also be affecting HIV care engagement. However, there is only one study we are aware of that qualitatively explored how the pandemic affected HIV services and care engagement from the perspectives of PWH in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In many settings, access to mental health services decreased during the COVID pandemic. 29,30 The Friendship Bench (FB) intervention is a lay health worker-led psychological intervention developed to close the treatment gap for common mental disorders (CMD) such as anxiety and depression in Zimbabwe. 31 The intervention reduced CMD symptoms in a cluster-randomized controlled trial in urban Zimbabwe, 31 where the prevalence of depression or anxiety is high.…”
Section: Introductionmentioning
confidence: 99%